LOCAL NEWS SOURCES IN THE IRAQI NEWSPAPERS: Local news sources in the Iraqi newspapers (An analytical study of local news sources In the newspaper Al-Zaman for the period from 1/6/2006 to 06/30/2006) - كاظم حسن سعد (ALBAHITH ALALAMI, 2022)
Local news is an important topic of the press because of its importance to readers. It touches their daily life in one way or another, which makes them interested in and followers of them. Hence the importance of local news, as it interests a wide segment of readers. There are many sources of newspapers for obtaining local news, as these sources are distributed to the newspaper’s own sources and external sources. Self-sources are the newspaper’s own sources, through which it is possible to obtain this news, such as the representatives of the newspaper and its correspondents and the journalists working in it. This is the example in this way. The external sources are distributed to local and international news agencies and satellite television terrestrial and satellite radio stations, newspapers and Alcilat.ovi this case, the newspaper does not make any effort distinguishes it from the rest of the media to get this news and me that she gets her ready from these sources. In our estimation, the more the newspaper is more dependent on its own sources for obtaining local news, the more successful and professional it is in the work of journalism and the disbelief of the work. Its uniqueness in obtaining this news is a reflection of the newspaper’s personality. This research is concerned with the local study of news sources in Iraqi newspapers by studying a specimen of her newspaper time for the purpose of the most important sources of knowledge adopted by the newspaper to get local news and whichever is more dependent self sources for a newspaper or Alforeigh.vdilaً sources for the study of local news in general and its importance For newspapers.